Development of Creative Product Designs Based on Local Wisdom - Erdoan, Aylin; Sok, Vanna; Dara, Ravi (Journal of Loomingulisus ja Innovatsioon, 2026)
Background: The development of creative product designs based on local wisdom is an essential aspect of preserving cultural heritage while fostering innovation in the global market. As consumer demand for unique and culturally resonant products increases, integrating local traditions and wisdom into product design can enhance both cultural identity and market competitiveness. This research explores the role of local wisdom in shaping creative product designs that are not only innovative but also reflective of regional values and aesthetics. Purpose: The purpose of this study is to investigate how local wisdom can be leveraged in the development of creative product designs. Specifically, it aims to examine the integration of cultural elements in the design process and its impact on both product innovation and consumer appeal. Methodology: A qualitative research design was employed, involving case studies of local artisans and designers who incorporate cultural motifs into their creations. Data were collected through interviews, observations, and analysis of product prototypes. Additionally, a comparative analysis was conducted between locally inspired designs and mainstream market products. Results: The findings reveal that products designed with local wisdom not only preserve cultural elements but also cater to contemporary consumer preferences for authenticity and sustainability. The incorporation of traditional craftsmanship and materials resulted in products that were perceived as more valuable and meaningful by consumers. Conclusion: Integrating local wisdom into creative product design offers significant potential for innovation while promoting cultural heritage. This approach can strengthen local economies by creating distinctive products that appeal to both domestic and international markets.